L’option Europe : une vue du long terme - Valaskakis, Kimon (L'Actualité économique, 1976)
AbstractThis article outlines the possibility of a "European option" as an alternative to strict continentalism leading to further integration with the U.S. It is argued that the benefits of such an European option are not immediately visible and by using narrow economic criteria with a short-run horizon, this option is not attractive. However by enlarging the evaluation criteria to include political and cultural considerations and by extending the time-horizon beyond the short into the long-run, the European connection appears very attractive indeed. Primarily the complementarity of Canada and Europe at the level of factors of production can be exploited and factor movements made to flow both ways. This coupled with the cultural and political dimensions make the European option both a feasible and desirable alternative to consider before throwing in the towel to continentalism.